2018
DOI: 10.4070/kcj.2017.0136
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Resistance to Intravenous Immunoglobulin Treatment and Coronary Artery Lesion in Patients with Kawasaki Disease: Analysis of the Korean Nationwide Multicenter Survey from 2012 to 2014

Abstract: Background and ObjectivesApproximately 10–15% of children with Kawasaki disease (KD) do not respond to initial intravenous immunoglobulin (IVIG) and have higher risk for coronary artery lesion (CAL). The aim of this study was to identify predictive factors from laboratory findings in patients who do not respond to IVIG treatment and develop CAL from KD.MethodsWe retrospectively collected nationwide multicenter data from the Korean Society of Kawasaki Disease and included 5,151 patients with KD between 2012 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…In future research, we will use the Z value to further verify these findings. In addition, CRP [45], WBC [46], PLT [47], hemoglobin [48], albumin [49], and total bilirubin [50] have been reported as risk factors for coronary artery damage. Further studies are needed to investigate the superiority of low-AAR compared to the above mentioned risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In future research, we will use the Z value to further verify these findings. In addition, CRP [45], WBC [46], PLT [47], hemoglobin [48], albumin [49], and total bilirubin [50] have been reported as risk factors for coronary artery damage. Further studies are needed to investigate the superiority of low-AAR compared to the above mentioned risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Since Kaneko et al 11 first reported NT-proBNP levels may associate with the development of CAL in KD, and it can be considered as a valuable biomarker to predict the risk of CAL in acute KD before initial IVIG treatment. Although a series of studies [12][13][14] on the diagnostic value of NT-proBNP to detect CAL of KD have been carried out in recent years, but they could not achieve a convincing result. Thus, we carried out this meta-analysis to ascertain the diagnostic accuracy of NT-proBNP in detecting CAL of KD in the acute period before initial IVIG treatment.…”
mentioning
confidence: 99%
“…In Korea, a retrospective study encompassing 795 KD patients by Ha et al 26 indicated that ANC was significantly higher in patients with CAA than in those without CAA, and CRP was significantly higher in complete KD patients than in incomplete KD patients. More persuasively, another nationwide survey from Korea enrolled 5,151 KD patients from 38 hospitals between 2012 and 2014 and found that IVIG‐nonresponsive patients had a significantly higher ANC and CRP when compared with their IVIG‐responsive counterparts, and moreover, CRP was subjected to a sky‐rocketing elevation in CAA patients 27 . To the best of our knowledge, little information on the possible variations of inflammatory mediators has been reported between CAA and NCA up to date.…”
Section: Discussionmentioning
confidence: 99%
“…More persuasively, another nationwide survey from Korea enrolled 5,151 KD patients from 38 hospitals between 2012 and 2014 and found that IVIGnonresponsive patients had a significantly higher ANC and CRP when compared with their IVIG-responsive counterparts, and moreover, CRP was subjected to a sky-rocketing elevation in CAA patients. 27 To the best of our knowledge, little information on the possible variations of inflammatory mediators has been reported between CAA and NCA up to date. In this context, one objective of the present study was to explore the above issue, and no significant differences were observed in inflammatory mediators between CAA and NCA according to our findings.…”
Section: Nca and Ivig Therapymentioning
confidence: 99%